Bisphosphonate use is associated with a decreased joint narrowing rate in the non-arthritic hip. Issue 11 (18th November 2022) - Kawai, Toshiyuki; Nishitani, Kohei; Okuzu, Yaichiro; Goto, Koji; Kuroda, Yutaka; Kuriyama, Shinichi; Nakamura, Shinichiro; Matsuda, Shuichi
Abstract : Aims: The preventive effects of bisphosphonates on articular cartilage in non-arthritic joints are unclear. This study aimed to investigate the effects of oral bisphosphonates on the rate of joint space narrowing in the non-arthritic hip. Methods: We retrospectively reviewed standing whole-leg radiographs from patients who underwent knee arthroplasties from 2012 to 2020 at our institute. Patients with previous hip surgery, Kellgren–Lawrence grade ≥ II hip osteoarthritis, hip dysplasia, or rheumatoid arthritis were excluded. The rate of hip joint space narrowing was measured in 398 patients (796 hips), and the effects of the use of bisphosphonates were examined using the multivariate regression model and the propensity score matching (1:2) model. Results: A total of 45 of 398 (11.3%) eligible patients were taking an oral bisphosphonate at the time of knee surgery, with a mean age of 75.8 years (SD 6.2) in bisphosphonate users and 75.7 years (SD 6.8) in non-users. The mean joint space narrowing rate was 0.04 mm/year (SD 0.11) in bisphosphonate users and 0.12 mm/year (SD 0.25) in non-users (p < 0.001). In the multivariate model, age (standardized coefficient = 0.0867, p = 0.016) and the use of a bisphosphonate (standardized coefficient = −0.182, p < 0.001) were associated with the joint space narrowing rate. After successfully matching 43 bisphosphonate users and 86 non-users, the joint narrowing rate was smaller in bisphosphonate users (p < 0.001). Conclusion: The use of bisphosphonates is associated with decreased joint degeneration in non-arthritic hips after knee arthroplasty. Bisphosphonates slow joint degeneration, thus maintaining the thickness of joint cartilage in the normal joint or during the early phase of osteoarthritis. Cite this article: Bone Joint Res  2022;11(11):826–834.